Measuring Immigration Policies: Preliminary Evidence from IMPALA - Michel Beine; Brian Burgoon; Mary Crock; Justin Gest; Michael Hiscox; Patrick McGovern; Hillel Rapoport; Eiko Thielemann (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper presents the methods and preliminary findings from IMPALA, a database that systematically measures the character and stringency of immigration policies. Based on a selection of data for six pilot countries between 1990 and 2008, we document the variation of immigration policies across countries and over time. We focus on three specific dimensions: the number of entry tracks for economic workers; the measurement and role of bilateral agreements that complement unilateral immigration policies; and aggregation procedures that allow for gauging the stringency of immigration regulations comparatively.
Keywords: G30; H24; H25; 330; immigration policies; stringency indexes; economic immigration; entry track